A influência da capoeira no desenvolvimento psicomotor de crianças - Brito, Andreyson Calixto de (2014)
Psychomotor development is characterized by a progressive and continuous process which takes the evolution of cognition, affectivity, motor skills, communication and sociability, as a whole, simultaneous and integrated. The study aimed to evaluate the effects of the practice of capoeira psychomotor development in infancy. The sample consisted of 54 students of the second year of the municipal elementary education schools in Fortaleza, aged 6-12 years divided into two groups: experimental group (14 male - 15 female) and group control (12 male - 13 female). Children in the experimental group were subjected to the practice of capoeira twice a week for 32 weeks, with 45 minutes each session, while the control group did not participate in capoeira classes. The BPM (Psychomotor Battery) was used to assess psychomotor development. The statistical tool used was the Statistical Package for Social Sciences (SPSS) version 20.0. The level of significance was set at p ≤ 0.05. The main conclusions of this study regarding the psychomotor development of the children were as follows: a) females had better results in almost all tests, the pre-test and post-test, with statistically significant differences for thin praxis, the group trial during pre-test, and the notion of the body, in both groups at post-test; b) the post-test, the experimental group performed better in both sexes in the seven factors evaluated; c) the experimental group showed improvements in performance from the first to the second assessment, with statistically significant differences in all tests for evaluation of psychomotor development: tone (p <0.01); equilibration (p <0.00); lateralization (p <0.00); notion of the body (p <0.00); spatiotemporal structure (p <0.00); global praxis (p <0.00) and thin praxis (p <0.00). From the results obtained in this study, we conclude that the practice of capoeira, when well targeted, delivers significant improvements in psychomotor development of children.